Współpraca wyższych uczelni z pracodawcami drogą do sukcesu absolwentów na rynku pracy - Zając, Bożena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The paper is an attempt od presenting different form of cooperation of universities and employers leading to increase of employability graduates, including those with disabilities. The problem of contemporary academic education is to assure suitability of education to employment of graduates, to open the educational process to labor market, and to shape such qualifications and skills that are needed by employers. In the content of the paper the advantages and barriers of cooperation with employers were presented. The main advantages are as follows (among others): increasing the recognition of universities among potential employers and candidates, increasing the quality of education and researches, increasing of chances of employment after graduation, building a net of contacts on business environment, increasing the quality of human capital, promoting images of companies as an attractive partner. Moreover, in the content of the paper the factors of obstacles of employability of people with disabilities were pointed out and characterized. The most important factors are combined with problems od administrative, financial, social, organizational, qualifications, information, infrastructural nature.